2020
DOI: 10.1002/biof.1609
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Emodin relieved lipopolysaccharide‐evoked inflammatory damage in WI‐38 cells by up‐regulating taurine up‐regulated gene 1

Abstract: Background: Neonatal pneumonia (NP) has a high fatality rate in neonatal illness. This research investigated the functions of emodin on lipopolysaccharide (LPS)-evoked inflammatory injury in WI-38 cells. Methods: Cell counting kit-8 (CCK-8) assay and flow cytometry were utilized for examining the impacts of LPS and emodin on viability and apoptosis, respectively. Taurine up-regulated gene 1 (TUG1) level was altered through cell transfection and investigated by reverse transcription quantitative polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…*** P<0.001 vs. LPS (-) + GLA (µM) (-); ### P<0.001 vs. LPS (+) + GLA (µM) (-) + Colivelin (µM) (-). ∆∆ P<0.01 and ∆∆∆ P<0.001 vs. LPS (+) + GLA (µM) ( 10 ) + Colivelin (µM) (-).…”
Section: Figurementioning
confidence: 93%
See 3 more Smart Citations
“…*** P<0.001 vs. LPS (-) + GLA (µM) (-); ### P<0.001 vs. LPS (+) + GLA (µM) (-) + Colivelin (µM) (-). ∆∆ P<0.01 and ∆∆∆ P<0.001 vs. LPS (+) + GLA (µM) ( 10 ) + Colivelin (µM) (-).…”
Section: Figurementioning
confidence: 93%
“…(C) Protein expression level of VE-cadherin, ZO-1 and claudin 5 in LPS-induced hPMVECs co-treated with GLA and colivelin was analyzed using western blot analysis. *** P<0.001 vs. LPS (-) + GLA (µM) (-); ### P<0.001 vs. LPS (+) + GLA (µM) (-) + Colivelin (µM) (-); ∆ P<0.05, ∆∆ P<0.01 and ∆∆∆ P<0.001 vs. LPS (+) + GLA (µM) ( 10 ) + Colivelin (µM) (-). hPMVECs, human pulmonary microvascular endothelial cells; GLA, glaucocalyxin A; LPS, lipopolysaccharide; VE-cadherin, vascular endothelial cadherin; ZO-1, zonula occludens-1.…”
Section: Figurementioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, the down-regulated expressions of Notch 1, Notch 2, Notch3, and the repressed phosphorylation of p65 and NF-κB induced by emodin were markedly reversed after TUG1 knockdown by transfection with sh-TUG1, which further consolidated the argument [ 33 ]. A most recent study in human fibroblasts cell line (WI-38) further demonstrated that emodin (5–20 μM) enhanced TUG1 expression and alleviated the LPS-evoked inflammatory damage via restraining the NF-κB and p38MAPK pathways [ 34 ].…”
Section: Pharmacological Effects Of Emodinmentioning
confidence: 99%